Living Labs for Public Sector Innovation: insights from a European case study - Anne Vorre Hansen; Lars Fuglsang; Christine Liefooghe; Luis Rubalcaba; David Gago; Ines Mergel; Nathalie Haug; Maria Taivalsaari Røhnebæk; Francesco Mureddu (Technology Innovation Management Review, 2022)
Living labs have gained increased attention in research and practice as both a practical and theoretical innovation phenomenon that emphasizes co-creation, real-life settings, and user/customer involvement. More recently, living labs have also emerged as a specific approach to open innovation processes in the context of publics across the EU. Nevertheless, it is still not clear how the understanding of living labs can be translated and organized into new sectorial settings, what type of public sector innovation challenges it addresses, and what role citizens and users have. The aim of this article is therefore to explore and analyze how living labs are applied as processes for public sector innovation. Based on a mixed method approach of 21 European living lab cases, the analysis reveals a pattern of three different processes for living lab organizational and actor roles: living labs organized as cross-sectorial collaboration, living labs emerging within the public sector as main initiator and beneficiary, and living labs developed by civil society actors. The findings are presented as three scenarios for implementing living labs, which also acts as a background for the article's final discussion about the potentials and pitfalls of living labs in public sector contexts.